Pengaruh Persentase Penduduk Tidak Sekolah dan Distribusi Pendapatan Terhadap Indeks Pembangunan Manusia - Kevin Andre Sipahutar; Leonardo Siahaan; Kiki Pramana; Esyha Nur Azizah; Andi Taufiq Umar (Economic Reviews Journal, 2024)
This study aims to analyze the impact of the percentage of non-schooling population and income distribution on the Human Development Index (HDI) in Indonesia. Using a quantitative method with multiple linear regression, data were taken from the official website of the Central Statistics Agency (BPS) including the percentage of non-schooling population, Gini coefficient, and HDI. The results show that both variables simultaneously have a significant effect on HDI (F calculated 37.79 > F table 4.26). Partially, only the percentage of the non-schooling population has a significant effect (sig = 0.0209 < 0.05), while income distribution does not (sig = 0.7961 > 0.05). This study emphasizes the importance of increasing access to education and reducing educational inequality to improve HDI in Indonesia..